Nanocrystalline magnetic powder core and preparation method thereof

CN119381107AInactive Publication Date: 2025-01-28ZHEJIANG TIANTONG ELECTRONIC INFORMATION MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411961277.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing magnetic powder cores are difficult to improve magnetic permeability while reducing losses, and traditional coatings are easy to cure at high temperatures, affecting density and performance.

Method used

The composite magnetic powder, including iron silicon boron copper nano crystals and cover layers, the cover layer consists of MNZN iron oxygen and epoxy -modified organic silicon resin. Crystal pink heart.

Benefits of technology

The magnetic guidance rate and density of nano -crystal magnetic powder have been improved, the high -frequency vortex losses are reduced, and they have excellent anti -aging performance, which is suitable for large -scale production of chemical industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of soft magnetic materials, and discloses a nanocrystalline magnetic powder core and a preparation method thereof. The preparation method comprises the following steps: putting the composite magnetic powder into a mold, and carrying out compression molding at the temperature of 90-110 DEG C and the pressure of 700-1000 MPa to obtain a primary product; the primary product is subjected to annealing treatment under the protective atmosphere, and a finished product nanocrystalline magnetic powder core is obtained; the composite magnetic powder comprises Fe-Si-B-Cu-Nb nanocrystals and a coating layer coating the Fe-Si-B-Cu-Nb nanocrystals; the coating layer comprises the following components: MnZn ferrite and epoxy modified organic silicon resin; the mass ratio of the MnZn ferrite to the Fe-Si-B-Cu-Nb nanocrystalline is (1-10): 100, and the mass ratio of the epoxy modified organic silicon resin to the Fe-Si-B-Cu-Nb nanocrystalline is (2-5): 100. According to the preparation method, the magnetic powder core with better soft magnetic performance can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic materials, in particular to a nanocrystalline magnetic powder core and a preparation method thereof. Background Art

[0002] Magnetic powder cores are mainly made by mixing and pressing magnetic powder and insulating coating agents. They have excellent characteristics such as high resistivity, high saturation magnetic induction intensity, high effective magnetic permeability, and good DC bias, which meet the development of electronic devices towards miniaturization, high power, and low loss. Nanocrystals have high magnetic permeability and low coercivity due to their low magnetostriction coefficient, and also have high resistivity, so high-frequency eddy current loss is low. They have been widely studied and applied to magnetic components such as transformers and inductors. With the development of electric power and electronic products, magnetic devices are gradually developing towards miniaturization, high power, and stable performance, which puts higher requirements on the performance and price of magnetic powder cores.

[0003] Traditional insulating coating materials are non-magnetic materials, which reduce the loss of magnetic powder cores while also reducing the magnetic permeability. Therefore, how to ensure that the loss of magnetic powder cores is reduced while improving their magnetic permeability is one of the current research directions of magnetic powder cores.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a nanocrystalline magnetic powder core and a preparation method thereof.

[0006] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a nanocrystalline magnetic powder core, comprising: The composite magnetic powder is placed in a mold and pressed at a temperature of 90-110°C and a pressure of 700-1000 MPa to obtain a primary product; The primary product is annealed in a protective atmosphere to obtain a finished nanocrystalline magnetic powder core; The composite magnetic powder includes iron, silicon, boron, copper, and niobium nanocrystals and a coating layer coated thereon; The coating layer comprises MnZn ferrite and epoxy-modified silicone resin; The mass ratio of MnZn ferrite to FeSiBCuNb nanocrystals is 1-10:100, and the mass ratio of epoxy-modified silicone resin to FeSiBCuNb nanocrystals is 2-5:100.

[0007] In an optional embodiment, placing the composite magnetic powder in the mold further includes obtaining the composite magnetic powder. The method for obtaining the composite magnetic powder includes: Dissolving MnZn ferrite and epoxy-modified silicone resin in a solvent to obtain a coating solution; The iron-silicon-boron-copper-niobium nanocrystals are uniformly mixed with the coating liquid, granulated, and then dried to obtain composite magnetic powder.

[0008] In an optional embodiment, the drying temperature is 50-60° C. and the time is 15-30 min.

[0009] In an optional embodiment, a lubricant is further added to the coating liquid, and the lubricant is selected from at least one of zinc stearate and mica powder.

[0010] In an optional embodiment, zinc stearate and mica powder are further added to the coating solution, the mass ratio of zinc stearate to iron silicon boron copper niobium nanocrystals is 0.1-0.3:100, and the mass ratio of mica powder to iron silicon boron copper niobium nanocrystals is 1-2:100.

[0011] In an optional embodiment, the solvent is anhydrous ethanol, and the mass ratio of the added amount of the solvent to the iron silicon boron copper niobium nanocrystals is 20-30:100.

[0012] In an optional embodiment, at least one of the following features (1) and (2) is included: (1) Annealing temperature is 400~520℃, and holding time is 60~120min; (2) The protective atmosphere is nitrogen.

[0013] In an optional embodiment, at least one of the following features (1) to (3) is included: (1) The chemical formula of Fe-Si-B-Cu-Nb nanocrystals expressed in terms of atomic ratio is Fe 73.5 Si 13.5 B9Cu1Nb3; (2) The particle size of Fe-Si-B-Cu-Nb nanocrystals is 15~25μm; (3) The particle size of MnZn ferrite is 1~5μm.

[0014] In an optional embodiment, the epoxy-modified silicone resin is a resin with the brand name SJ-804.

[0015] In a second aspect, the present invention provides a nanocrystalline magnetic powder core, which is prepared by the preparation method of any one of the aforementioned embodiments.

[0016] The present invention has the following beneficial effects: The addition of MnZn ferrite can enhance the magnetic permeability of nanocrystalline magnetic powder cores. The hardness of FeSiBCuNb nanocrystals and MnZn ferrite decreases at 90-110°C, and high-density magnetic powder cores can be obtained by pressing at this temperature. Epoxy-modified silicone resin is used as a coating agent, which will not solidify at 90-110°C and has better fluidity. The problem of being unable to obtain high-density magnetic powder cores due to easy solidification at high temperatures of silicone resin or epoxy resin as a coating agent will not occur. After curing, the epoxy-modified silicone resin can form a highly cross-linked three-dimensional network structure on the surface of the magnetic powder, which is beneficial to the insulation between the powders and reduces high-frequency eddy current losses. In addition, the epoxy-modified silicone resin also has excellent anti-aging properties. FeSiBCuNb nanocrystals are corrosion-resistant, and MnZn ferrite is a magnetic insulating material. Therefore, before pressing, the magnetic powder does not need to be passivated, which is convenient for production. In addition, the temperature of the pressing process is not too high, and the equipment requirements are not high, so it can be mass-produced industrially.

[0017] Therefore, the preparation method provided by the present invention has a simple process flow, can produce a magnetic powder core with low loss and high magnetic permeability, and the process is suitable for large-scale production. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0020] Based on the problems existing in the current traditional magnetic powder core, the inventors have made the following considerations: MnZn ferrite materials have high magnetic permeability and high resistivity, and can replace traditional non-magnetic insulating coating materials. However, MnZn ferrite materials have high hardness. Since nanocrystals themselves also have the characteristics of high hardness, if the added MnZn ferrite also has high hardness, it will be more difficult to obtain high-density magnetic powder cores by conventional cold pressing, resulting in poor soft magnetic properties of nanocrystalline magnetic powder cores. Considering high-temperature pressing, nanocrystals and MnZn ferrites become soft at high temperatures, making it easy to produce high-density magnetic powder cores. However, the coating agents added to the manufacture of magnetic powder cores are generally silicone resins or epoxy resins. These resins will solidify at high temperatures and have poor fluidity, making it difficult to achieve magnetic powder core pressing and molding, or causing the density of the magnetic powder core to be low. In addition, pressing at too high a temperature will have high requirements for equipment conditions due to the high temperature, which is not conducive to large-scale industrial production.

[0021] Therefore, the following solution is proposed: An embodiment of the present invention provides a method for preparing a nanocrystalline magnetic powder core, comprising: The composite magnetic powder is placed in a mold and pressed at a temperature of 90-110°C and a pressure of 700-1000 MPa to obtain a primary product; Annealing the preliminary product under a protective atmosphere to obtain a finished nanocrystalline magnetic powder core; The composite magnetic powder comprises iron, silicon, boron, copper, and niobium nanocrystals and a coating layer coated thereon; The coating layer comprises MnZn ferrite and epoxy-modified silicone resin; The mass ratio of the MnZn ferrite to the FeSiBCuNb nanocrystals is 1-10:100, and the mass ratio of the epoxy-modified silicone resin to the FeSiBCuNb nanocrystals is 2-5:100.

[0022] The preparation method provided by the invention can enhance the magnetic properties of the nanocrystalline magnetic powder core by adding MnZn ferrite. The hardness of FeSiBCuNb nanocrystalline and MnZn ferrite decreases at 90-110 DEG C, and a high-density magnetic powder core can be obtained by pressing at this temperature. Epoxy-modified organic silicone resin is used as a coating agent, which will not solidify at 90-110 DEG C and has better fluidity, and the problem that the high-density magnetic powder core cannot be obtained due to the easy solidification of silicone resin or epoxy resin as a coating agent at high temperature will not occur. After curing, the epoxy-modified organic silicone resin can form a highly cross-linked three-dimensional network structure on the surface of the magnetic powder, which is beneficial to the insulation between the powders and reduces the high-frequency eddy current loss. In addition, the epoxy-modified organic silicone resin also has excellent anti-aging performance. The FeSiBCuNb nanocrystalline is corrosion-resistant, and the MnZn ferrite is a magnetic insulating material. Therefore, before pressing, it is not necessary to passivate the magnetic powder, and the production is convenient. In addition, the temperature of the pressing process is not too high, the equipment requirements are not high, and large-scale industrial production can be carried out.

[0023] It should be noted that the amount of MnZn ferrite added needs to be within the range required by the present invention. If too little is added, the effect of improving the magnetic properties of the nanocrystalline magnetic powder core is not obvious. If too much is added, it will cause agglomeration, resulting in an increase in high-frequency eddy current loss. The amount of epoxy-modified silicone resin added also needs to be within the range required by the present invention. If too little is added, it is difficult to form. If too much is added, the magnetic permeability will be reduced.

[0024] It should be noted that the pressing temperature of the present invention needs to be within the above range. If the temperature is too low, the powder fluidity is poor and the density of the magnetic powder core is low. If the pressing temperature is too high, the epoxy-modified silicone resin may solidify or the equipment requirements may be too high.

[0025] Preferably, the iron silicon boron copper niobium nanocrystals are water vapor-atomized iron silicon boron copper niobium nanocrystal powders, which have excellent properties of high resistivity, high saturation magnetic induction intensity, low coercivity and low loss.

[0026] Preferably, in order to obtain a magnetic powder core with better magnetic properties, the chemical formula of Fe-Si-B-Cu-Nb nanocrystals expressed by atomic ratio is Fe 73.5 Si 13.5 B9Cu1Nb3.

[0027] Preferably, in order to ensure that the obtained magnetic powder core has a better density and obtain better performance, the particle size of the iron silicon boron copper niobium nanocrystal is 15-25 μm; Preferably, in order to make the MnZn ferrite more uniformly coated, the particle size of the MnZn ferrite is 1-5 μm.

[0028] Optionally, to ensure that the coating layer has better coating properties for the nanocrystals and better fluidity at the pressing temperature, the epoxy-modified silicone resin is a resin with the brand name SJ-804.

[0029] The preparation method is specifically as follows: S1, insulation coating A certain mass of MnZn ferrite powder and epoxy modified silicone resin are dissolved in a solvent, and a proper lubricant is added to obtain a coating solution. The FeSiBCuNb nanocrystalline powder and the coating solution are evenly mixed and granulated, and then dried to obtain a composite magnetic powder with an insulating coating layer.

[0030] Optionally, the lubricant is selected from at least one of zinc stearate and mica powder. The addition of the lubricant can assist in the compaction of the magnetic powder core.

[0031] Optionally, to better assist the pressing of the magnetic powder core and ensure that other properties of the magnetic powder core are not affected, the lubricant includes zinc stearate and mica powder, the mass ratio of the zinc stearate to the iron silicon boron copper niobium nanocrystals is 0.1-0.3:100, and the mass ratio of the mica powder to the iron silicon boron copper niobium nanocrystals is 1-2:100.

[0032] Alternatively, the solvent may be selected as anhydrous ethanol.

[0033] Optionally, the mass ratio of the added amount of anhydrous ethanol to the nanocrystalline magnetic powder core is 20-30:100.

[0034] Optionally, the drying temperature is 50-60°C and the drying time is 15-30 minutes.

[0035] S2, warm pressing The composite magnetic powder is evenly loaded into the mold, the pressing temperature is set to 90-110°C, the pressure is set to 700-1000Mpa, and the pressure is maintained for 10-30s to obtain the initial product.

[0036] S3, annealing The pressed and formed primary product is placed in a heating furnace and annealed in an inert atmosphere, with the temperature raised to 400-520°C at a heating rate of 10°C / min, and kept at that temperature for 60-120 minutes. Then, the product is cooled in the furnace to obtain a nanocrystalline magnetic powder core.

[0037] Optionally, the inert atmosphere is nitrogen or argon.

[0038] The nanocrystalline magnetic powder core provided in the embodiment of the present invention is prepared by the preparation method provided by the present invention.

[0039] The present invention will be further described below in conjunction with specific embodiments.

[0040] Example 1 This embodiment provides a method for preparing a nanocrystalline magnetic powder core, specifically: (1) Insulation coating: by weight, 2 parts of MnZn ferrite (chemical formula MnZnFe2O4) powder with a particle size of 1-5 μm, 2.5 parts of epoxy modified silicone resin (brand name SJ-804), 0.15 parts of zinc stearate, 1 part of mica powder and 20 parts of anhydrous ethanol were mixed evenly to obtain a coating solution; 100 parts of Fe with a particle size of 15~25μm 73.5 Si 13.5 The B9Cu1Nb3 nanocrystalline powder is evenly mixed with the coating liquid, and then mixed and granulated, and then baked at 50°C for 30 minutes to obtain composite magnetic powder; (2) Warm pressing: The composite magnetic powder is warm pressed in a mold at a temperature of 90°C, a molding pressure of 850 MPa, and a holding time of 30 seconds to form a ring-shaped magnetic powder core with an outer diameter of 10.2 mm, an inner diameter of 5.1 mm, and a height of 3 mm. (3) Annealing treatment: The pressed magnetic powder core is subjected to stress relief annealing in a nitrogen atmosphere at an annealing heating rate of 10°C / min. After stress relief annealing at 450°C for 80 min, the core is furnace cooled to room temperature to obtain a nanocrystalline magnetic powder core.

[0041] Example 2 This embodiment provides a method for preparing a nanocrystalline magnetic powder core, specifically: (1) Insulation coating: by weight, 3 parts of MnZn ferrite (chemical formula MnZnFe2O4) powder with a particle size of 1-5 μm, 3 parts of epoxy modified silicone resin (brand name SJ-804), 0.2 parts of zinc stearate, 0.2 parts of mica powder and 25 parts of anhydrous ethanol were mixed evenly to obtain a coating solution; 100 parts of Fe with a particle size of 15~25μm 73.5 Si 13.5 The B9Cu1Nb3 nanocrystalline powder is evenly mixed with the coating liquid, and then mixed and granulated, and then baked at 60°C for 15 minutes to obtain composite magnetic powder; (2) Warm pressing: The composite magnetic powder is warm pressed in a mold at a temperature of 100°C, a molding pressure of 920 MPa, and a holding time of 30 seconds to form a ring-shaped magnetic powder core with an outer diameter of 10.2 mm, an inner diameter of 5.1 mm, and a height of 3 mm. (3) Annealing treatment: The pressed magnetic powder core is subjected to stress relief annealing in a nitrogen atmosphere at a heating rate of 10°C / min. After stress relief annealing at 480°C for 100 min, the core is furnace cooled to room temperature to obtain a nanocrystalline magnetic powder core.

[0042] Example 3 This embodiment provides a method for preparing a nanocrystalline magnetic powder core, specifically: (1) Insulation coating: by weight, 3 parts of MnZn ferrite (chemical formula MnZnFe2O4) powder with a particle size of 15-25 μm, 2.8 parts of epoxy modified silicone resin (brand name SJ-804), 0.25 parts of zinc stearate, 0.15 parts of mica powder and 25 parts of anhydrous ethanol were mixed evenly to obtain a coating solution; 100 parts of Fe with a particle size of 15~25μm 73.5 Si 13.5 The B9Cu1Nb3 nanocrystalline powder is evenly mixed with the coating solution, and then mixed and granulated, and then baked at 55°C for 10 minutes to obtain composite magnetic powder; (2) Warm pressing: The composite magnetic powder is warm pressed in a mold at a temperature of 110°C, a molding pressure of 980 MPa, and a holding time of 30 seconds to form a ring-shaped magnetic powder core with an outer diameter of 10.2 mm, an inner diameter of 5.1 mm, and a height of 3 mm. (3) Annealing treatment: The pressed magnetic powder core is subjected to stress relief annealing in a nitrogen atmosphere at a heating rate of 10°C / min. After stress relief annealing at 510°C for 90 min, the core is cooled to room temperature in the furnace to obtain a nanocrystalline magnetic powder core.

[0043] Example 4 This embodiment is basically the same as Embodiment 1, except that: The amount of MnZn ferrite powder used is 1 part by weight, and the amount of epoxy-modified silicone resin used is 2 parts by weight.

[0044] Example 5 This embodiment is basically the same as Embodiment 1, except that: The amount of MnZn ferrite powder used is 10 parts by weight, and the amount of epoxy-modified silicone resin used is 5 parts by weight.

[0045] Comparative Example 1 This comparative example does not add MnZn ferrite and adopts cold pressing.

[0046] (1) Insulation coating: By weight, 3 parts of epoxy modified silicone resin (brand name SJ-804), 0.2 parts of zinc stearate, 0.15 parts of mica powder and 25 parts of anhydrous ethanol were mixed evenly to obtain a coating liquid; 100 parts of Fe with a particle size of 15~25μm 73.5 Si 13.5 The B9Cu1Nb3 nanocrystalline powder is uniformly mixed with the coating solution, and then mixed and granulated, and then baked at 55°C for 10 minutes to obtain composite magnetic powder; (2) Cold pressing: The composite magnetic powder is placed in a mold with a molding pressure of 800 MPa and a holding time of 30 seconds to form a ring-shaped magnetic powder core with an outer diameter of 10.2 mm, an inner diameter of 5.1 mm, and a height of 3 mm. (3) Annealing treatment: The pressed magnetic powder core is subjected to stress relief annealing in a nitrogen atmosphere at an annealing heating rate of 10°C / min. After stress relief annealing at 400°C for 120 min, the core is furnace cooled to room temperature to obtain a nanocrystalline magnetic powder core.

[0047] Comparative Example 2 In this comparative example, no MnZn ferrite was added and the steel was pressed at warm pressure.

[0048] (1) Insulation coating: By weight, 3.5 parts of epoxy modified silicone resin (brand name SJ-804), 0.15 parts of zinc stearate, 0.2 parts of mica powder and 25 parts of anhydrous ethanol were mixed evenly to obtain a coating liquid; 100 parts of Fe with a particle size of 15~25μm 73.5 Si 13.5 The B9Cu1Nb3 nanocrystalline powder is uniformly mixed with the coating solution, and then mixed and granulated, and then baked at 55°C for 10 minutes to obtain composite magnetic powder; (2) Warm pressing: The composite magnetic powder is warm pressed in a mold at a temperature of 110°C, a molding pressure of 900 MPa, and a holding time of 30 seconds to form a ring-shaped magnetic powder core with an outer diameter of 10.2 mm, an inner diameter of 5.1 mm, and a height of 3 mm. (3) Annealing treatment: The pressed magnetic powder core is subjected to stress relief annealing in a nitrogen atmosphere at a heating rate of 10°C / min. After stress relief annealing at 500°C for 100 min, the core is furnace cooled to room temperature to obtain a nanocrystalline magnetic powder core.

[0049] Comparative Example 3 This comparative example is basically the same as Example 3, except that cold pressing is adopted, the pressing temperature is room temperature 25° C., and the thickness of the obtained magnetic powder core is 3.11 mm.

[0050] Comparative Example 4 This comparative example is basically the same as Example 3, except that high-temperature pressing is adopted, the pressing temperature is 150° C., and the thickness of the obtained magnetic powder core is 3.06 mm.

[0051] Comparative Example 5 This comparative example is basically the same as Example 3, except that the resin is replaced by epoxy resin (brand EP-301) instead of epoxy-modified silicone resin, and the thickness of the obtained magnetic powder core is 3.10 mm.

[0052] Experimental example The properties of the magnetic powder cores prepared in various embodiments and comparative examples were tested. The density was measured by the Archimedean drainage method, the effective magnetic permeability was measured by an impedance analyzer, and the loss was measured by a soft magnetic AC measuring instrument.

[0053] Record the test results in Table 1.

[0054] Table 1 Test results of magnetic powder cores of various embodiments and comparative examples

[0055] Comparing the data of Example 1 with that of Comparative Example 3, the density and magnetic permeability of the magnetic powder core of Comparative Example 3 are significantly lower than those of Example 1, and the loss is higher than that of Example 1, indicating that it is difficult to obtain a magnetic powder core with higher density by cold pressing due to the hardness of nanocrystals and ferrites. Comparing the data of Example 1 with that of Comparative Example 4, the density and magnetic permeability of the magnetic powder core of Comparative Example 4 are significantly worse than those of Example 1, indicating that the pressing temperature is too high, which may make it difficult to press due to the solidification of the resin, and thus it is difficult to obtain a magnetic powder core with better performance. Comparing the data of Example 1 with that of Comparative Example 5, the density and magnetic permeability of the magnetic powder core of Comparative Example 5 are significantly worse than those of Example 1, indicating that it is difficult to obtain a magnetic powder core with better performance by using conventional resins, such as epoxy resin, according to the pressing method provided by the present invention.

[0056] In summary, the manufacturing method provided by the present invention can produce a magnetic powder core with high density and high magnetic properties, and the manufacturing process does not require passivation treatment of the magnetic powder, so the production is convenient; the production process does not have high requirements on equipment and can be mass-produced industrially.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocrystalline magnetic powder core, characterized in that: include: The composite magnetic powder is placed in a mold and pressed at a temperature of 90-110°C and a pressure of 700-1000 MPa to obtain a primary product; Annealing the preliminary product under a protective atmosphere to obtain a finished nanocrystalline magnetic powder core; The composite magnetic powder includes iron, silicon, boron, copper, and niobium nanocrystals and a coating layer coated thereon; The coating layer comprises MnZn ferrite and epoxy-modified silicone resin; The mass ratio of the MnZn ferrite to the FeSiBCuNb nanocrystals is 1-10:100, and the mass ratio of the epoxy-modified silicone resin to the FeSiBCuNb nanocrystals is 2-5:

100.

2. The method for preparing a nanocrystalline magnetic powder core according to claim 1, characterized in that: Placing the composite magnetic powder in the mold also includes obtaining the composite magnetic powder. The method for obtaining the composite magnetic powder includes: Dissolving the MnZn ferrite and the epoxy-modified silicone resin in a solvent to obtain a coating solution; The iron-silicon-boron-copper-niobium nanocrystals are uniformly mixed with the coating liquid, granulated, and then dried to obtain the composite magnetic powder.

3. The method for preparing a nanocrystalline magnetic powder core according to claim 2, characterized in that: The drying temperature is 50~60℃ and the time is 15~30min.

4. The method for preparing a nanocrystalline magnetic powder core according to claim 2, characterized in that: A lubricant is also added to the coating liquid, and the lubricant is selected from at least one of zinc stearate and mica powder.

5. The method for preparing a nanocrystalline magnetic powder core according to claim 2, characterized in that: Zinc stearate and mica powder are also added to the coating liquid, the mass ratio of the zinc stearate to the iron silicon boron copper niobium nanocrystals is 0.1-0.3:100, and the mass ratio of the mica powder to the iron silicon boron copper niobium nanocrystals is 1-2:

100.

6. The method for preparing a nanocrystalline magnetic powder core according to claim 2, characterized in that: The solvent is anhydrous ethanol, and the mass ratio of the added amount of the solvent to the iron silicon boron copper niobium nanocrystals is 20-30:

100.

7. The method for preparing a nanocrystalline magnetic powder core according to claim 1, characterized in that: The invention comprises at least one of the following features (1) and (2): (1) Annealing temperature is 400~520℃, and holding time is 60~120min; (2) The protective atmosphere is nitrogen.

8. The method for preparing a nanocrystalline magnetic powder core according to claim 1, characterized in that: Includes at least one of the following features (1) to (3): (1) The chemical formula of the Fe-Si-B-Cu-Nb nanocrystals expressed in terms of atomic ratio is Fe 73.5 Si 13.5 B9Cu1Nb3; (2) The particle size of the Fe-Si-B-Cu-Nb nanocrystals is 15-25 μm; (3) The particle size of the MnZn ferrite is 1-5 μm.

9. The method for preparing a nanocrystalline magnetic powder core according to claim 1, characterized in that: The epoxy-modified silicone resin is a resin with the brand name SJ-804.

10. A nanocrystalline magnetic powder core, characterized in that: The nanocrystalline magnetic powder core is prepared by the method for preparing the nanocrystalline magnetic powder core as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing soft magnetic metal composite via warm compaction

    CN104036907A

  • Method for preparing iron-silicon-aluminum soft magnetic powder core through warm-pressing

    CN105344993A

  • Preparation method of organic-inorganic composite insulation coated iron powder core

    CN108711482A

  • Composite iron-silicon-aluminum soft magnetic powder core and preparation method thereof

    CN111696745A

  • Insulation coating method for magnetically soft alloy powder

    CN113223845A